2002
DOI: 10.1038/modpathol.3880499
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmune Gastritis: Distinct Histological and Immunohistochemical Findings Before Complete Loss of Oxyntic Glands

Abstract: Autoimmune gastritis (AG) can be easily recognized when the histological features are fully developed, but recognizing AG before the complete loss of the oxyntic mucosa is more challenging. One feature of fully developed AG is enterochromaffin cell-like (ECL) hyperplasia, but its presence or absence in earlier stages of AG has not been fully evaluated. A retrospective study of biopsy specimens from 40 patients was performed; all of the patients were originally diagnosed with possible AG based on the presence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
33
2
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(45 citation statements)
references
References 21 publications
8
33
2
2
Order By: Relevance
“…These results correspond well with the findings of anti-H,KATPase reactivity of antigastric autoantibodies in H. pylori gastritis just mentioned [17] and support the idea that in genetically susceptible individuals H. pylori infection triggers or accelerates the development of gastric autoimmunity [6]. Thus, H. pylori gastritis could progress to autoimmune gastritis via an intermediate stage described as active autoimmune gastritis without complete loss of glands [76,82]. This concept is strengthened by observations that this particular pre-atrophic phenotype of autoimmune gastritis improves after H. pylori therapy [58].…”
Section: Immunopathology Of Atrophic Gastritissupporting
confidence: 91%
“…These results correspond well with the findings of anti-H,KATPase reactivity of antigastric autoantibodies in H. pylori gastritis just mentioned [17] and support the idea that in genetically susceptible individuals H. pylori infection triggers or accelerates the development of gastric autoimmunity [6]. Thus, H. pylori gastritis could progress to autoimmune gastritis via an intermediate stage described as active autoimmune gastritis without complete loss of glands [76,82]. This concept is strengthened by observations that this particular pre-atrophic phenotype of autoimmune gastritis improves after H. pylori therapy [58].…”
Section: Immunopathology Of Atrophic Gastritissupporting
confidence: 91%
“…Clinical studies showed that the hypergastrinemia was common in the patients with type A gastritis and gastric body cancer. 28,29 To clarify the relationship between gastrin and p16 in vivo, we first detected the expression of p16 in primary gastric body carcinoma by immunohistochemistry (86 cases, 25 early and 61 advanced gastric cancer patients). The results showed that the p16 protein was abundantly expressed in gastric cancer cell and mainly located in cytoplasm, compared with that in surrounding normal tissue (Figs.…”
Section: Gradual Downregulation Of P16 In Primary Gastric Body Carcinomamentioning
confidence: 99%
“…Az intestinalis metaplasia ebben a szakaszban ritka és gócos. A parietalis sejtek számának nem egyértelmű csökkenésével járó korai AMAG jó jelzője a lamina propria mirigypusztulással járó, mély és diffúz lymphoplasmocytás beszű-rődése, az epithelialis metaplasia, a lineáris enterochromaffi n-like (ECL) -sejtes hyperplasia és a parietalis sejtek pseudohypertrophiája [17].…”
Section: áBraunclassified